Retrospective Study of Horn Cancer in Cattle - Dave, Harshad A; Vadalia, Jignesh V; Vagh, Arshi A; Bhatt, Raghuvir H; Dodia, Vaibhav D (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This retrospective study was carried out to evaluate the incidence of horn cancer in cattle presented at the Veterinary Clinical Complex of  the College at Junagadh (Gujarat, India) over a three-year period (January 2021 to December 2023). During the study period, 30,664 cases  were registered across all species, with 5,975 cases involving cattle across various clinical disciplines. Among that 2,405 cases (40.25%)  were categorized as surgical, among which 149 cases (6.19%) were diagnosed and treated for horn cancer. The highest incidence of horn  cancer was found in the age group 6 to 10 years (52.35 %), followed by 11 to 15 years (39.60 %), 16 to 20 years (4.03 %), 21 to 25 years  (2.01 %), and 0 to 5 years (2.01 %). Horn cancer was observed more in males (Bullocks 91/93 and Bulls 2/93) than in females (56/149).  A breed-wise higher incidence was observed in Gir cattle (39.60 %), followed by Kankrej cattle (36.91 %) and non-descript cattle  (23.49 %). There was an almost similar involvement of the left (49.66 %) side and right-side horn (50.33 %).
Keywords: Age, Breed, Cattle, Horn cancer, Retrospective analysis.